Functional and Structural Characterization of Novel Type of Linker Connecting Capsid and Nucleocapsid Protein Domains in Murine Leukemia Virus - Doležal, Michal; Hadravová, Romana; Kožíšek, Milan; Bednárová, Lucie; Langerová, Hana; Ruml, Tomáš; Rumlová, Michaela (The Journal of biological chemistry, 2016)
The assembly of immature retroviral particles is initiated in the cytoplasm by the binding of the structural polyprotein precursor Gag with viral genomic RNA. The protein interactions necessary for assembly are mediated predominantly by the capsid (CA) and nucleocapsid (NC) domains, which have conserved structures. In contrast, the structural arrangement of the CA-NC connecting region differs between retroviral species. In HIV-1 and Rous sarcoma virus, this region forms a rod-like structure that separates the CA and NC domains, whereas in Mason-Pfizer monkey virus, this region is densely packed, thus holding the CA and NC domains in close proximity. Interestingly, the sequence connecting the CA and NC domains in gammaretroviruses, such as murine leukemia virus (MLV), is unique. The sequence is called a charged assembly helix (CAH) due to a high number of positively and negatively charged residues. Although both computational and deletion analyses suggested that the MLV CAH forms a helical conformation, no structural or biochemical data supporting this hypothesis have been published. Using an in vitro assembly assay, alanine scanning mutagenesis, and biophysical techniques (circular dichroism, NMR, microcalorimetry, and electrophoretic mobility shift assay), we have characterized the structure and function of the MLV CAH. We provide experimental evidence that the MLV CAH belongs to a group of charged, E(R/K)-rich, single α-helices. This is the first single α-helix motif identified in viral proteins.
Keywords: sekundární struktura proteinů; Leukemia Virus, Murine; virové plášťové proteiny; murine leukemia virus (MLV); nuclear magnetic resonance (NMR); single alpha-helix (SAH); Mutagenesis; capsid protein (CA); virus myší leukemie; Mice; Capsid Proteins; spacer peptide (SP); Protein Domains; retrovirus; charged assembly helix (CAH); Protein Structure, Secondary; zvířata; virus assembly; myši; circular dichroism (CD); electron microscopy (EM); mutageneze; proteinové domény; Animals